The Objective Structural Clinical Examination (OSCE) on assessment clinical practice skills in the achievement of Maternal-newborn and midwifery practicum I - Sripoun, Sureepron; Srewongchai, Lumpong; Tanintithiphong, Pornravin; Tangpant, Chotip; Discharoen, Kruawan (Journal of Public Health Nursing, 2022)
The Objective Structural Clinical Examination (OSCE) is a method that can be assessed clinical skill and truly differentiated individual learners’ skill level. The objective of this classroom research aimed to study the clinical skill of nursing students according to OSCE method in Maternal-newborn and midwifery practicum 1 subject and to study satisfaction of nursing students to OSCE method. The participants were 71 third year nursing students. Instruments included clinical scenarios, checklist form for clinical skills assessment and satisfaction questionnaire of learners. Data were analyzed by descriptive statistics. The results of clinical skill assessment by using OSCE method found that most students were able to practice vaginal delivery assistant skill at an excellent level (74.7%), followed by newborn care skill (67.6%), and Leopold’s maneuver skill (57.8%) respectively. Students were satisfied with the overall OSCE method at the highest level ( = 4.8, SD .20) and they found that OSCE method was useful for practical application. The results shown that OSCE method can be used to assess students’ performance individually and useful for nursing practice. Therefore, this method should be developed and used in further assessment of students in nursing practicum subject.